From Safeguarding to Global Circulation: Intellectual Property, Digital Transformation, and the Cross-Border Reconfiguration of Chinese Intangible Cultural Heritage - Wang, Weiyi; Zhao, Fengyu (Asia Pacific Economic and Management Review, 2026)
As intangible cultural heritage (ICH) becomes increasingly visible in global cultural, creative, and digital markets, questions surrounding ownership, interpretation, and sustainable transmission have taken on new urgency. This article offers an integrated review of the evolving intersections among ICH, intellectual property protection (IPP), and globalization, with a specific focus on China—the world’s most active ICH-bearing nation. Drawing on legal scholarship, bibliometric studies, ethnographic research, and emerging digital-innovation literature, the study develops two analytical frameworks: a pathway model tracing how ICH is transformed into cultural intellectual property within domestic institutional settings, and a multi-level embedding model explaining how ICH is reinterpreted and reorganized in destination cultural and legal environments. Findings highlight three major tensions. First, the ontological mismatch between ICH and IP systems—most notably the conflict between the communal nature of heritage and the novelty requirements of patent law—generates persistent dilemmas around collective authorship, dynamic evolution, and cultural obligations. Second, cross-border dissemination produces both opportunities for global visibility and risks of cultural discount, symbolic dilution, and inequitable benefit-sharing. Third, while digitalization and generative AI provide novel modes of revitalization, they also raise concerns about data sovereignty, algorithmic appropriation, and community exclusion. The study argues that effective governance requires culturally sensitive IP strategies, participatory decision-making mechanisms, and ethical digital infrastructures that ensure the sustainability of living heritage. By bridging fragmented research strands, this article contributes a comprehensive theoretical and empirical foundation for understanding how Chinese ICH navigates the legal, cultural, and technological conditions of the global era.